Family characteristics and governance of small and medium-sized family firms - Felício, J. Augusto; Galindo Villardón, Maria Purificación (Journal of Business Economics and Management, 2015)
The purpose of this paper is to study the influence of family characteristics on the governance of small and medium-sized family firms. The study presents and tests a theoretical model resorting to data on 151 Portuguese SMEs. The study uses nonlinear principal component analysis by alternating least squares, bivariate analysis and cluster analysis. Family characteristics influence governance mechanisms and family firms form clusters based on family characteristics and governance mechanisms. The results reveal that family characteristics are a source of heterogeneity among family firms which corroborates the criticism on family firms’ homogeneity assumption. The identification of clusters of firms constitutes a reference for family firms’ definition of governance models. The originality of the paper relies on the analysis of specific family characteristics and its importance as a source of family firms’ heterogeneity is proven. This study opens new insights on family firms’ governance research and may be extended to other family characteristics and overall implications on performance.